Penerapan Algoritma Fuzzy Mamdani Terhadap Penentuan Modulus Young Kain Spandex - Anwar, Khoiril; Amiruddin, Muhammad (Innovative: Journal Of Social Science Research, 2024)
Customer satisfaction is certainly closely related to the quality of a product. The better the product quality, the higher customer satisfaction. One of the production qualities of fabrics can be reviewed from the properties of flexibility which is based on the value of Young's modulus. In determining the Young modulus of a product, the most important aspect is the standard operating of production machines. This aspect is reviewed from the speed of the yarn roll and the temperature of the production machine. In this study, a type of spandex fabric was used with a yarn percentage of 72% Nylon and 28% Polyester. With this, the author conducted a study related to the Application of the Fuzzy Logic Algorithm Method. The study utilized Matlab software due to its wide range of tools available for the Mamdani method, the research successfully predicted the young modulus with a Mean Absolute Percentage Error (MAPE) of 3,25%, this indicate a high accuracy level of 96,75%. This shows that the fuzzy logic of the Mamdani method is very accurate to predict the value of the young modulus in plain fabrics at PT Honggang Textile Fujian, China.